An effective antioxidant defense provides protection against zinc deficiency‐induced oxidative stress in Zn‐efficient maize plants. Issue 5 (24th May 2019) - Tewari, Rajesh K.; Kumar, Praveen; Sharma, Parma Nand
Abstract: Maize plants ( Zea mays L. cv. Ganga 2 and cv. Jaunpuri satha) were grown in solution culture under glasshouse conditions at deficient (0 µM) and normal (1 µM) levels of Zn supply. Appearance of visible effects characteristic of Zn deficiency, depression in plant growth, and dry matter yield of the plants indicated that Ganga 2 was more susceptible to Zn deficiency than Jaunpuri satha. Higher susceptibility of Ganga 2 to Zn deficiency was also manifested by a greater decrease in plant dry mass and an increased accumulation of TBARS (thiobarbituric acid reactive substance, describing lipid peroxidation). While total SOD activity was decreased in Zn deficient plants of Ganga 2, it was increased marginally in case of Jaunpuri satha. The marginal increase in total SOD activity in the Zn‐deficient Jaunpuri satha plants was a result of a marked increase in non‐CuZn SOD and only a slight decrease in CuZn SOD. Though Zn deficiency increased H2 O2 concentration and the activities of H2 O2 ‐scavenging enzymes in both the cultivars, there was less increase in H2 O2 concentration and the activities of peroxidase, ascorbate peroxidase and glutathione reductase were more prominently increased in the Zn‐efficient Jaunpuri satha. Plants of the susceptible variety, Ganga 2, accumulated higher concentrations of glutathione disulfide. It is concluded that the significant decreases in the activities of CuZn SOD (CN‐sensitive SOD) and glutathione reductase, and high concentrations of H2 O2 predisposed Zn‐deficient Ganga 2 plants to more severe oxidative stress than those of Jaunpuri satha and, therefore, contributed to a greater decrease in dry matter production.